2009
DOI: 10.1016/j.ygeno.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specific differentially methylated regions (TDMR): Changes in DNA methylation during development

Abstract: Tissue specific differentially methylated regions (TDMRs) were identified and localized in the mouse genome using second generation virtual RLGS (vRLGS). Sequenom MassARRAY quantitative methylation analysis was used to confirm and determine the fine structure of tissue specific differences in DNA methylation. TDMRs have a broad distribution of locations to intragenic and intergenic regions including both CpG islands, and non-CpG islands regions. Somewhat surprising, there is a strong bias for TDMR location in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 44 publications
3
100
0
2
Order By: Relevance
“…The role of DNA methylation as a locking mechanism for an important event, such as tissue-specific gene expression during development, is well established (8,27,20). In particular, several studies of single muscle genes (2,12,18,37) have demonstrated a role of hypomethylation in the induction of muscle differentiation (21,29,31).…”
Section: Discussionmentioning
confidence: 99%
“…The role of DNA methylation as a locking mechanism for an important event, such as tissue-specific gene expression during development, is well established (8,27,20). In particular, several studies of single muscle genes (2,12,18,37) have demonstrated a role of hypomethylation in the induction of muscle differentiation (21,29,31).…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for this discrepancy include the differences inherent in measuring mRNA versus protein, differences in species (mouse and human), and differences in tissue-type (whole 9.5 dpc embryo and neuroblastoma samples). Furthermore, this particular locus has previously been identified to be differentially methylated in different tissues (Song et al, 2009), raising the possibility that the relationship between Zscan10 methylation and expression may in fact be tissue-specific.…”
Section: Discussionmentioning
confidence: 99%
“…C57 BL/6J mice were purchased from Jackson Laboratory and maintained at Charles River Laboratories, Inc. (Yokohama, Japan). Brain specimens of the mice at three differential stages (15-day-old embryo; E15, new born; NB, 12-week adult; AD), were collected and stored as described previously (11).…”
Section: Methodsmentioning
confidence: 99%
“…The CpG sites at CpG island (CpGi) of the Zfp206-exon 5 (human: ZNF206-exon 5) are reported as a testicular and neuronal-specific DMRs and they are demethylated during late stage of mouse brain and testis development (5,11). Here, we found that methylation state of the region associated with the ZNF206 expression and the homologous CpGi was aberrantly hypomethylated in human neuroblastomas, especially those with poor prognostic patients.…”
Section: Introductionmentioning
confidence: 91%